829 IMPACT OF SODIUM-GLUCOSE COTRANSPORTER-2 INHIBITORS ON CARDIAC REMODELLING IN LOW RISK PATIENTS WITH TYPE 2 DIABETES MELLITUS. (15th December 2022) - Del Giudice, Carmen; Fabiani, Dario; D´aquino Malvezzi, Marco Caracciolo; Scognamiglio, Gabriella; Pezzullo, Enrica; Caso, Valentina; Castagnola, Patrizia; Volpe, Alessandra; Liccardo, Biagio; Nigro, Gerardo; Golino, Paolo; Russo, Vincenzo
Abstract: Background: Sodium-glucose cotransporter 2 inhibitors (SGLT2i) are associated to a reduced risk of major adverse cardiovascular events in type 2 diabetes mellitus (T2DM) patients. Subclinical left ventricular (LV) systolic disfunction has been observed in DM patients, even if ejection fraction is preserved. The impact of SGLT2i on cardiac structure and function is still unclear. Our aim was to evaluate the effects of SGLT2i on LV remodelling and global longitudinal strain (GLS) in patients with well compensated TIIDM. Methods: Between November 2021 to April 2022, we prospectively evaluated 35 consecutives subjects with TIIDM in need of SGLT2i according to their referring physician. Main inclusion criteria were preserved ejection fraction (EF>50%), no history of heart failure and coronary artery disease, and the lack of moderate to severe valvular heart disease and chronic kidney disease (EGFR <50%). Conventional and speckle tracking echocardiography were performed at baseline and after 6 months of treatment. Results: 17 patients have been evaluated for statistical analysis (6% F, mean age 65± 9 years). GLS (p=0, 007) and EF (p=0.01) reached statistically significance after 6 months therapy. Moreover on ECG analysis, we found significant reduction in P-wave dispersion (p =0.019). However no statistically significant changes in diastolic function parameters and Myocardial Work indices have been found. Conclusions: Our study showed that SGLT2i treatment in people with T2DM may display a positive effect on LV remodelling and improve GLS, even in patients with low-risk DM. Keywords : Diabetes mellitus; SGLT2 inhibitors; Speckle tracking echocardiography; Left ventricular systolic function; Cardiac remodelling.